Immunohistochemical and functional characterization of nitric oxide signaling pathway in isolated aorta from Crotalus durissus terrificus - Monica, Fabiola Z.; Rojas-Moscoso, Julio; Porto, Marcovan; Schenka, Andre A.; Antunes, Edson; Cogo, Jose Carlos; De Nucci, Gilberto [UNESP] (Elsevier B.V., 2012)
We characterized the nitric oxide (NO)-cyclic GMP-phosphodiesterase-5 (PDE5) pathway in Crotalus durissus terrificus aorta. Concentration responses curves to acetylcholine (ACh), sodium nitroprusside (SNP), BAY41-2272 (soluble guanylyl cyclase [sGC] stimulator), BAY60-2770 (sGC activator) and tadalafil (PDE5 inhibitor) were constructed in phenylephrine (10 mu M)-precontracted tissues with intact (E+) or denuded (E-) endothelium. ACh (0.0001-10 mu M) and SNP (0.0001-10 mu M) relaxed aorta, which were reduced by the NO synthase (L-NAME,100 mu M) or the sGC inhibitors (ODQ 10 mu M). Tadalafil (0.0001-10 mu M) relaxed E+ rings with potency (pEC(50)) and maximal response (E-max) values of 7.34 +/- 0.02 and 105 +/- 8%, respectively. E- or ODQ treatment significantly (P < 0.05) reduced tadalafil relaxations (66 +/- 18% and 71 +/- 7%, respectively). BAY41-2272 (0.0001-300 nM) produced concentration-dependent relaxations in E+ rings, which were reduced by addition of either ODQ or L-NAME (16.0- and 5.2-fold rightward shifts, respectively). The relaxation of BAY60-2770 was markedly potentiated by ODQ and L-NAME (41.0- and 9.7-fold leftward shifts, respectively), whereas in E- the pEC(50) values were shifted by 7-fold to the right. Immunohistochemistry, followed validation by transcriptomic analysis, revealed the presence of eNOS in endothelium, whereas nNOS was observed only in perivascular nerves. sGC and PDE5 were expressed in smooth muscle. Thus, NO-sGC-PDE5 pathway is evolutionarily present in Crotalus sp. vessels, and has a remarkable degree of functional similarity to mammalian vessels. (C) 2011 Elsevier Inc. All rights reserved.
Keywords: Aorta; Crotalus durissus; Nitric oxide synthase; Phosphodiesterase type 5; Soluble guanylyl cyclase